2010
DOI: 10.3354/meps08490
|View full text |Cite
|
Sign up to set email alerts
|

At-sea movement patterns and diving behavior of Peruvian boobies Sula variegata in northern Peru

Abstract: GPS loggers and time-depth recorders were used to characterize the foraging behavior of the sexually dimorphic Peruvian booby Sula variegata on 2 islands in northern Peru. We evaluated whether (1) its foraging behavior differed from tropical boobies and temperate gannets (the Peruvian boobies feed in areas of enhanced productivity and high fish density), and (2) females and males exploited different foraging habitats as a consequence of size dimorphism. Birds foraged only during daylight hours, 1 to 3 times a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 50 publications
2
36
0
3
Order By: Relevance
“…Our results are in accordance with those of other studies which investigated sex difference in foraging activity (Phalan et al 2007;Zavalaga et al 2010) and trip length (Ramos et al 2009). Nevertheless, males dived more frequently than females during nighttime.…”
Section: Effect Of Daytime and Sex On Foraging Effortsupporting
confidence: 83%
“…Our results are in accordance with those of other studies which investigated sex difference in foraging activity (Phalan et al 2007;Zavalaga et al 2010) and trip length (Ramos et al 2009). Nevertheless, males dived more frequently than females during nighttime.…”
Section: Effect Of Daytime and Sex On Foraging Effortsupporting
confidence: 83%
“…We found little sex-specific differences in foraging characteristics in Peruvian boobies, as did Zavalaga et al (2010b); however, they displayed a significant difference in size, females being 16% heavier and 5% larger than males (Table 1). Boobies are well known to display a reversed sexual dimorphism (Nelson 1978), and several studies have found sex differences in foraging behaviour in several species (Lewis et al 2005, Zavalaga et al 2007, Weimerskirch et al 2009a and have suggested that they are related to the extent that sexual dimorphism exists for some foraging features, such as dive depths or foraging duration, or to different roles in parental investment.…”
Section: Sex-specific Differencesmentioning
confidence: 82%
“…Masked and red-footed boobies at Tromelin Island demonstrated a low degree of fidelity in successive foraging trips, a strategy that likely reflects the dynamic, unpredictable nature of prey patches associated with sub-surface marine predators (Weimerskirch 2007). High fidelity to foraging sites has been demonstrated in Peruvian boobies (Sula variegata; Zavalaga et al 2010) and other marine predators (Baduini et al 2006, Baylis et al 2008, Call et al 2008, Pettex et al 2010. However, these studies were all conducted in high productivity environments.…”
Section: Dive Depths and Dietmentioning
confidence: 99%